NEW PERSPECTIVES ON COMPOSITIONALITY: KIT FINE’S SEMANTIC RELATIONIST APPROACH TO MEANING. AN EXPOSITORY ESSAY (Analele Universității București.Filosofie, 2025)
The paper is an expository essay in which I run an assessment of compositionality from the vantage point of Kit Fine’s semantic relationist approach to meaning. This relationist view is deepening our conception about how the meanings of propositions depend not only on the semantic features and roles of each separate meaningful unit in a complex, but also on the relations that those units hold to each other. The telling feature of the formal apparatus of this Finean relationist syntax and semantics, viz. the coordination scheme, has some unexpected consequences that will emerge against the background of an analogy with the counterpart theoretic semantics for modal languages. In the evaluation of a de re modal formula at a world in a counterpart theoretic model, as opposed to the evaluation in a possible world semantic model, one may choose different possible objects as referents or semantic values of two tokens of a single type individual constant or individual variable. Likewise, in the relationist semantics for variables or individual constants (proper names), within a coordination schema one may choose different objects if the variables or the constants are not strictly coordinated. I shall leave the working out of this comparison for a future paper. The program defends ‘referentialism’ in philosophy of language; Fine holds that semantic relations that have to be added to the assigned intrinsic values in our semantictheory, especially the relation which he calls ‘coordination’, can do much of the work of (Fregean) sense. A relationist referentialism has certain important explanatory virtues which it shares with the Fregean position, but the former is better off ontologically thanthe latter, since it is not committed to the existence of sense.